1992
DOI: 10.1111/j.1469-8749.1992.tb08567.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial Paroxysmal Rhabdomyolysis: Management of Two Cases of the Non‐exertional Type

Abstract: SUMMARY Familial paroxysmal rhabdomyolysis with myoglobinuria is a rare and life‐threatening disease of young children, of unknown aetiology. Attacks bear no relation to exercise, are usually triggered by intercurrent infections and are often severe. The authors describe two cases and suggest plans for the prevention and management of attacks. Fasting appears to be the crucial factor precipitating attacks, but is not associated with hypoglycaemia or with a defect in lactate production, ketogenesis or fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Although the elevation occurred on different days after dose 1, these two subjects experienced the elevation within one calendar day of each other. This may suggest a commonality, environmental or genetic, that has not been uncovered [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Although the elevation occurred on different days after dose 1, these two subjects experienced the elevation within one calendar day of each other. This may suggest a commonality, environmental or genetic, that has not been uncovered [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of lipodystrophy has been postulated to be from redundancy in the roles the LIPIN proteins have in triacylglycerol synthesis in human adipocytes [109]. Genetic dissection demonstrated that it is the lack of Lipin1 PAP activity, rather than co-activator activity, that drives the altered lipid metabolism that results in lipodystrophy in mice [110][111][112]. Thus, PAP activity is needed for normal adipocyte differentiation and triacylglcerol synthesis.…”
Section: Pathogenesis Of Majeed Syndromementioning
confidence: 99%